The Use of Users' Personal Data to Improve Online Retail Services: An Analysis from a Systematic Literature Review - Lira, Danilo; Mac'Hamilton, Gabriel; Stadtler, Gabriel; Almeida, Myllena; Santos, Simone C. dos; Vilela, Jéssyka (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2023)
Context: The rise of online retail systems is increasingly evident, bringing users the convenience of shopping anywhere and at better prices than physical stores. Problem: As part of the online shopping process, several user data are frequently collected at registration or while browsing and making purchases. However, it is not always clear to the online consumer how this data is used and what benefits this sharing brings. Solution: This study aims to understand what personal data is being collected from online consumers, how it is being used, and the positive and negative impacts on the services provided to the user from the sharing of personal data. IS Theory: This work was conceived under the aegis of Argumentation Theory, presenting data (facts and opinions) from primary studies on the subject, evidence that proves the legitimacy of these data, and conclusions in the form of assertions or statements. Method: The research has a descriptive character and qualitative analysis, applying the systematic literature review method. Summary Results: From 52 studies, the results showed a great diversity of personal and browsing data collected, mainly during the purchase process, and used to define behavior patterns and offer personalized services. As a negative impact, there is a concern with data privacy and a lack of awareness of how online seller uses personal data. IS Contributions and Impact: As a main contribution, we highlight an enlightening discussion of how consumer data is used to improve online retail services, identifying quality studies on the topic, and supporting IS researchers.